2019
DOI: 10.3390/ma12162606
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Variation Small Angle Neutron Scattering Investigation of Micro- and Nano-Sized TATB

Abstract: Small angle neutron scattering (SANS) with contrast variation was used to characterize the fractal behavior and embedded porosity of micro/nano-sized 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) crystallites, gauging the effects of particle sizes on the microstructural features. Scattering results reveal that the external surface of micro-sized TATB crystallites are continuous and smooth interfaces and their internal pores display a surface fractal structure (surface fractal dimension 2.15 < DS < 2.25), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…According to the results in Table 1, it can be found that for smaller particle size, large porosity and specific surface area can be obtained, which is consistent with the results of Song et al. [29]. It can be seen from these results that particle size can affect the structure of nano pores in LLM‐105.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…According to the results in Table 1, it can be found that for smaller particle size, large porosity and specific surface area can be obtained, which is consistent with the results of Song et al. [29]. It can be seen from these results that particle size can affect the structure of nano pores in LLM‐105.…”
Section: Resultssupporting
confidence: 87%
“…The results show that the pore volume per unit mass of LLM-105 increases with the decrease of the particle size, and the increase of pore volume when the particle size decreases from micron to 500 nm is much larger than that when the particle size decreases from 500 nm to 200 nm. According to the results in Table 1, it can be found that for smaller particle size, large porosity and specific surface area can be obtained, which is consistent with the results of Song et al [29]. It can be seen from these results that particle size can affect the structure of nano pores in LLM-105.…”
Section: Analysis Of Internal Pore Structuresupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, by considering a succession of power-law decays interleaved with Guinier regions, one can describe hierarchically structured systems. This succession forms the basis of Beaucage [43,44] and Guinier-Porod [45] models, which are widely used as empirical models to analyze SAS data from random fractal and particulate systems, such as those occurring in some amphiphilic triblock polyelectrolytes [46], rocks [47], fertilizers encapsulated by starch-based superabsorbent polymers [48], silica-filled silicone rubber [49], aerosol nanoparticles [50] or micro/nano-sized TATB crystallites [51].…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of the sensitivity of ultra-fine explosives is the key to their performance in applications. According to the hot spot theory, the selectivity of the sensitivity is highly related to the size and number of defects in explosives [ 4 , 5 ]. A lot of numerical simulation works have reported the process of forming hot spots from defects in explosives such as atomic scale local distortion structures and nano pores [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%